Clear cell carcinoma: a comprehensive literature review of 254 cases. Issue 6 (June 2022) - Desai, A.; Faquin, W.C.; Iafrate, A.J.; Rivera, M.N.; Jaquinet, A.; Troulis, M.J.
Abstract: This comprehensive literature review represents a summary of all cases of clear cell carcinoma (CCC) of the salivary glands that are documented in the literature. PubMed was used to collect available reports of CCC; 97 reports detailing 254 cases, published between 1983 and 2020, were retrieved. Clinically the tumor manifests most commonly as a painless mass or swelling on the palate, and the duration of symptoms prior to seeking care ranges from 1 week to 6 years. Metastasis, both local and distant, was reported in 13.9% of 202 total cases. Local tumor recurrence was present in 18.8% of the cases. By histopathology, CCC shows a mixture of growth patterns including solid (25.1%), nested (78.6%), sheet-like (23.5%), cords (46.1%), and trabeculae (42.4%). Immunohistochemical studies are positive for one or more cytokeratins (99.1%), PAS (95.1%), EMA (77.8%), and p63 (96.3%), but negative for S-100 (96.3%), PASD (91.1%), SMA (91.0%), and calponin (95.1%). Molecular features were reported in 115 cases; 96.0% were positive for an EWSR1 rearrangement by EWSR1 break apart FISH testing and 14.8% were positive for the rearrangement EWSR1–ATF1 tested by qPCR or targeted RNA sequencing. Clinical patterns and genetic studies imply that this tumor is the extraosseous counterpart of clear cell odontogenic carcinoma, an intraosseous odontogenic tumor of the jaws.